Entomocomplex of Radish in Open-field Cultivation in the Central Part of the Right-Bank Forest-Steppe of Ukraine - Shchetina, S.; Mostoviak, I.; Fedorenko , V. (Quarantine and plant protection, 2024)
Goal. To specify the species composition of insect pests affecting radish (Raphanus sativus (L.) convar. radicula (Pers) Sazon.) in open-field cultivation conditions in the central part of the Right-Bank Forest-Steppe of Ukraine. Methods. The study was conducted following commonly accepted methods in entomology and vegetable growing. From 2008 to 2022, we investigated the species diversity of insects, dominant species, their abundance, and the structure of the harmful entomocomplex in radish crops grown in open-field conditions on household plots and farms in the Cherkasy region. Results. In the entomological complex of radish, 59 species of phytophagous insects from 20 families and 8 orders were identified: Coleoptera — 29%, Lepidoptera — 27%, Homoptera — 15%, Diptera — 10%, Orthoptera — 9%, Thysanoptera — 5%, Hemiptera — 3%, Hymenoptera — 2%. Sixteen dominant species of phytophagous insects were found in radish crops, including diamondback moth (Plutella maculipennis Curt.), crucifer flea beetles (Phyllotreta cruciferae Goeze), striped flea beetle (Phyllotreta undulata Kutsch.), cabbage white butterfly (Pieris brassicae L.), turnip moth (Agrotis segetum Denis&Schiff.) and owlet moth (Lacanobia oleracea L.), crucifer shield bug (Eurydema ventralis Kol.), cabbage aphid (Brevicoryne brassicae L.), spring root maggot (Delia brassicae Bouche) and summer root maggot (Delia floralis Fallen), seedcorn maggot (Delia platura Mg.), sawfly (Athalia rosae L.), stem weevil (Ceutorrhynchus quadridens Panz.), tobacco thrips (Thrips tabaci Lindeman), turnip sawfly (Entomoscelis adonidis Pallas), and crucifer webworm (Evergestis extimalis Scop.). Through multi-year studies, the periods of insect damage corresponding to radish developmental stages were determined. The most critical damage to radish plants by harmful insects occurred during the initial stages of development (ВВСН 0—9) and from emergence to the growth and formation of the root crop (BBCH 42—48). Conclusions. It was found that among the identified phytophagous insects in radish crops, the most economically significant damage was caused by the cabbage aphid, crucifer flea beetles, striped flea beetle, spring cabbage fly, and seedcorn maggot. On average over the research period (2008—2022), the largest areas of radish crops were infested by the diamondback moth, crucifer flea beetles, and striped flea beetle, cabbage white butterfly, winter and owlet moths, cabbage shield bug, and cabbage aphid, ranging from 5% to 80%, reaching a maximum in some years up to 60—100% of the area.